Efektivitas Media Counting Box untuk Meningkatkan Kemampuan Penjumlahan bagi Peserta Didik Disabiitas Intelektual Ringan - Ramadhani, Hurul Aini; Irdamurni, Irdamurni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The counting box media is a form of contact media made from cardboard and plywood that is used to easily understand addition material correctly and well. This article discusses the effectiveness of the counting box media in improving the addition skills of students with mild intellectual disabilities at SLB Al Azhar Bukittinggi. This research uses a quantitative approach with a Single Subject Research (SSR) method designed as A-B-A. The results of the research conducted show that in the baseline phase, 25% was achieved in three meetings. In the baseline phase (A1), there were 8 meetings with scores of 65%, 80%, 80%, 90%, 90%, 95%, 95%, 95%, and in the baseline phase (A2), there were three meetings with a score of 95%. It can be concluded that the use of the counting box media is effective in improving the addition skills of students with mild intellectual disabilities at SLB Al Azhar Bukittinggi.